2003
DOI: 10.1021/ma030026l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chain End and Molecular Weight on Molecular Motion of Polystyrene, Revealed by the ESR Selective Spin-Label Method

Abstract: A local segmental mobility was determined by electron spin resonance (ESR) spin-label method for a series of polystyrene (PS) with various molecular weights. Each PS specimen was selectively spin-labeled with stable nitroxide radicals at a chain end or inside sites. Molecular motion at the inside of the chain was compared with that at the chain end from the temperature dependence of ESR spectra of the nitroxide radicals. The transition temperature of molecular motion, T 5.0mT, at which the extreme separation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(83 citation statements)
references
References 36 publications
3
76
0
Order By: Relevance
“…As an example, Kajiyama et al [6] reported that polymer surface enriched with segregated chain ends exhibited higher molecular mobility, in other words, lower glass-rubber transition temperature (T g ) as evidenced by atomic force measurement. Miwa et al [7] spin-labeled selectively at particular sites and detected the molecular mobility of each site. Figure 8.1 shows chemical structures of spin-labeled polystyrene (PS) at the inside and the end of chain segments.…”
Section: Glass-rubber Transition Detected By the Spin Label Methods Fomentioning
confidence: 99%
See 3 more Smart Citations
“…As an example, Kajiyama et al [6] reported that polymer surface enriched with segregated chain ends exhibited higher molecular mobility, in other words, lower glass-rubber transition temperature (T g ) as evidenced by atomic force measurement. Miwa et al [7] spin-labeled selectively at particular sites and detected the molecular mobility of each site. Figure 8.1 shows chemical structures of spin-labeled polystyrene (PS) at the inside and the end of chain segments.…”
Section: Glass-rubber Transition Detected By the Spin Label Methods Fomentioning
confidence: 99%
“…In general, the splitting between Chemical structure of spin-labeled PS at inside (left) and end (right) of chain. The figure is adapted from [7] with permission from the American Chemical Society the outer-most lines of the main triplet spectrum due to the nitrogen hyperfine coupling becomes narrower with an increase in the mobility of the radicals because of the motional averaging of the anisotropy. The extreme separation width shown with arrows in Fig.…”
Section: Glass-rubber Transition Detected By the Spin Label Methods Fomentioning
confidence: 99%
See 2 more Smart Citations
“…Second, as discussed in Section 4.3, the AgNWs act as heterogeneous nucleating sites and lead to shorter polymer chains. As a result, the segmental mobility of the chains increases accounting for lower T g [64]. …”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%